Foliar application of exogenous gibberellin or cytokinin mitigates salinity stress on faba bean (Vicia faba L.) - Hossam S. EL-BELTAGI; Mohamed F. EL-NADY; Ahmed M. ISMAIL; Elsayed A. E. ABOMARZOKA; Mohamed M. EL-MOGY; Metwaly M. S. METWALY (Notulae Botanicae Horti Agrobotanici Cluj-Napoca)
Soil salinity significantly impairs plant development by reducing the availability of water and essential nutrients. This study explores the potential of gibberellin (GA) and cytokinin (CK) in mitigating detrimental effects of salinity stress on faba bean. Seeds were sown in saline soil, and plants were subjected to foliar applications of GA and CK at concentrations of 25 and 50 mg L-1. Results revealed that both hormones significantly enhanced key growth attributes, including plant height, total leaf area, and dry biomass. Moreover, chlorophyll (chl. a, b, total chl.) content increased alongside elevated levels of proline, total phenols, crude protein, membrane stability, and macronutrient (NPK) concentrations. Gibberellin and CK treatments also promoted branching and flowering, while reducing the percentage of flower shedding. In terms of yield-related traits, significant improvements were observed in seed yield per hectare, weight of 100-seed, seed number/pod, seed weight per pod, and overall reduction in flower drop. The most significant enhancements in the evaluated traits were recorded with the application of GA and CK at a concentration of 50 mg L-1 during both seasons. These findings highlight the effectiveness of GA and CK in strengthening salt tolerance mechanisms and boosting the productivity of faba bean under saline conditions.